OKRs for all : making objectives and key results work across your organization - Vellore, Vetri (John Wiley & Sons, Inc., 2022)
"The Objectives and Key Results (OKR) framework is gaining popularity and has helped some of the world's most successful businesses find a solution to their strategic execution problems. Many businesses are moving to implement the framework popularized by John Doerr's Measure What Matters, but most don't actually know how to use it. They often use OKR's as top-down directives to be revisited once or twice a quarter. That changes little, and continues to let goals, data, projects, tactics become fractured by disparate tech stacks, preferences, and siloed departments just like before. To make a real impact, OKR's should be the tool that guides the decision-making of every team on a daily basis, not just quarterly at an executive level. This book will explain how to make that happen. It will guide senior leaders in designing and rolling out an OKR system from the bottom of their organization up, and help managers and teams organize their daily decision-making around those shared goals. We'll share case studies from companies you know and love, best practices, and pitfalls to avoid. We'll outline how they do it, sharing the seven-part blueprint for a strategic execution framework that puts purpose at the center of everything, and giving you the playbook to put it into action. The result will an organization united in strategic execution with teams that are more engaged and working in parallel. And the results will show on the bottom line."--